Stability of the Posteromedial Fragment in a Tibial Plateau Fracture - Immerman, Igor; Bechtel, Christopher; Yildirim, Gokce; Heller, Yonah; Walker, Peter S.; Egol, Kenneth A. (The Journal of Knee Surgery, 2013)
The posteromedial fragment in tibial plateau fractures is considered unstable and requires specific fixation. However, if not loaded by the femur, it may remain stable and not require additional fixation. Our purpose was to determine the size of the posteromedial fragment that would remain unloaded by the femoral-tibial contact area, as a function of fracture line orientation and knee flexion angle. Seven human cadaveric knees with intact capsule and ligaments were mounted in a mechanical rig and flexed from 0 to 30, 90, 105, and 120 degrees of flexion. The fiducial points and articular surfaces were digitized, and 3-dimensional software models of the knees at each flexion angle were created. The femoral-tibial contact areas were determined using the software under high- and low-load conditions. Posteromedial fragments of various sizes and fracture line orientations relative to the posterior femoral condylar axis (PFCA) were modeled, and their locations relative to contact areas were determined. The size of unloaded fragments decreased with increased flexion angle. Fragments occupying 60% of the medial plateau were loaded at all angles, but fragments with 30% of the plateau became loaded at 90 degrees under high load and 120 degrees under low load. Fracture line orientations of 0 to 20 degrees external rotation relative to PFCA allowed for the largest fragments to remain unloaded. The size of posteromedial tibial plateau fracture fragment that remains unloaded by the femur varies with knee flexion angle and fracture line orientation. This may have implications for the management of posteromedial tibial plateau fractures.
Keywords: tibial plateau fracture; Posteromedial fragment; Contact area; fracture stability